1993
DOI: 10.1161/01.hyp.22.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Role of pressure natriuresis in long-term control of renal electrolyte excretion.

Abstract: If pressure natriuresis is to play an important role in arterial pressure control, renal perfusion pressure must have a long-term effect on urinary sodium excretion. The aim of this study was to quantitate the importance of renal perfusion pressure per se in controlling renal hemodynamics and electrolyte excretion chronically. Female mongrel dogs (n=6) were instrumented with bilateral renal artery catheters for measurement of renal perfusion pressure and occluders on both renal arteries for servo-control of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
0
31
0
1
Order By: Relevance
“…Moreover, weight reduction lowered plasma renin activity and aldosterone concentration in obese subjects. 34 In our study of obese dogs, plasma renin activity was elevated more than twofold after 5 weeks of a high-fat diet despite marked sodium retention and increased extracellular fluid volume. 45 The failure to suppress Ang II levels despite volume expansion and hypertension suggests that there may be a powerful underlying stimulus for renin secretion in the development of obesity.…”
Section: Role Of the Renin-angiotensin System In Obesitymentioning
confidence: 50%
See 1 more Smart Citation
“…Moreover, weight reduction lowered plasma renin activity and aldosterone concentration in obese subjects. 34 In our study of obese dogs, plasma renin activity was elevated more than twofold after 5 weeks of a high-fat diet despite marked sodium retention and increased extracellular fluid volume. 45 The failure to suppress Ang II levels despite volume expansion and hypertension suggests that there may be a powerful underlying stimulus for renin secretion in the development of obesity.…”
Section: Role Of the Renin-angiotensin System In Obesitymentioning
confidence: 50%
“…34 Because both kidneys were exposed to the same neurohumoral influences, these studies were able to measure the effects of long-term changes in renal perfusion pressure per se on renal hemodynamics and electrolyte excretion. These studies indicated that relatively small changes in renal perfusion pressure caused large alterations in renal sodium and water excretion that persisted as long as renal artery pressure was altered.…”
Section: Pressure Natriuresis Is a Key Component Of Renal-body Fluid mentioning
confidence: 99%
“…8,11 Strong experimental support for this notion comes from a study in dogs in which the renal perfusion pressure to 1 kidney was servocontrolled at a reduction in pressure comparable to that achieved in the present study. 18 Throughout the duration of this study (12 days), there was a sustained reduction in sodium excretion in the kidney with the reduced renal perfusion pressure and an increase in sodium excretion in the high-pressure contralateral kidney. Because both kidneys were exposed to the same neurohumoral influences, this study supports a premise that has been difficult to test experimentally and one that is critical to the renal body fluid feedback mechanism: that renal perfusion pressure is an important long-term controller of sodium excretion.…”
Section: Discussionmentioning
confidence: 83%
“…21 Because the 2 kidneys in each animal were exposed to the same neurohumoral influences, these studies were able to quantitate the chronic effects of small changes in renal perfusion pressure per se on electrolyte excretion and renal hemodynamics. These studies demonstrated that relatively small changes in renal artery pressure cause large alterations in sodium and water excretions that persisted as long as renal artery pressure was altered (12 days).…”
Section: Chronic Effects Of Renal Perfusion Pressure On Excretion Of mentioning
confidence: 99%